Egg production performance, egg yolk antioxidant profile and excreta concentration of corticosterone in golden pheasants (Chrysolophus pictus) fed diets containing different levels of green vegetables. Issue 5 (9th November 2016) - Kullu, S. S.; Das, A.; Bajpai, S. K.; Garg, A. K.; Yogi, R. K.; Saini, M.; Sharma, A. K.
Summary: In order to study the effect of feeding graded levels of green vegetables on egg production performance and egg yolk antioxidant status, 27 female golden pheasants (GP) were randomly distributed into three groups of nine each in an experiment based on completely randomized design. The diets of the birds in groups T1, T2 and T3 contained 1.4%, 2.7% and 5.0% of green vegetables respectively. Feeding of experimental diets started on 12th February (day 1) and was continued till 30 June 2012. Average number of eggs laid and egg mass produced by the hens in group T3 was higher (p < 0.004) than those of T1 and T2 . Hen day egg production was lowest (p < 0.001) in group T1 . Roche yolk colour score was highest (p < 0.01) in T3 followed by T2 and was lowest in T1 . Other external and internal egg quality parameters were similar among the groups. Total antioxidant capacity (TAC) of egg yolk was higher (p < 0.04) in group T3 as compared to other two groups. Egg yolk concentration of total carotenoids, β ‐carotene, total sulfhydryl, protein‐bound sulfhydryl and non‐protein‐bound sulfhydryl was higher (p < 0.05), whereas concentration of malondialdehyde was lower (p < 0.024) in group T3 as compared to other two groups. Excreta concentration of corticosterone was highest (p < 0.012) in T1, followed by T2, and was lowest in T3 . Egg yolk concentration of TAC and TSH was positively and that of malondialdehyde was negatively correlated with carotenoids intake. Excreta concentration of corticosterone was negatively correlated with carotenoids intake. It was concluded that incorporation of green vegetables in the diet at 5% on dry matter basis would improve egg production, egg yolk antioxidant status and the ability of the captive GP to combat stress.